2021
DOI: 10.1111/anae.15563
|View full text |Cite
|
Sign up to set email alerts
|

SARS‐CoV‐2 infection and venous thromboembolism after surgery: an international prospective cohort study

Abstract: SARS-CoV-2 has been associated with an increased rate of venous thromboembolism in critically ill patients. Since surgical patients are already at higher risk of venous thromboembolism than general populations, this study aimed to determine if patients with peri-operative or prior SARS-CoV-2 were at further increased risk of venous thromboembolism. We conducted a planned sub-study and analysis from an international, multicentre, prospective cohort study of elective and emergency patients undergoing surgery dur… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 95 publications
(54 citation statements)
references
References 13 publications
1
51
0
Order By: Relevance
“…If there is a ‘ceiling effect’ of VTE risk in patients undergoing emergency surgery, we might expect a smaller increased risk of VTE in patients with SARS‐CoV‐2 infection undergoing emergency vs. elective surgery. Data presented in this article confirm this [ 6 ]. In patients undergoing emergency surgery, those with peri‐operative SARS‐CoV‐2 infection have only a slight increase in VTE risk compared with those without (OR = 1.26).…”
Section: Effect Of Venous Thromboembolismsupporting
confidence: 89%
“…If there is a ‘ceiling effect’ of VTE risk in patients undergoing emergency surgery, we might expect a smaller increased risk of VTE in patients with SARS‐CoV‐2 infection undergoing emergency vs. elective surgery. Data presented in this article confirm this [ 6 ]. In patients undergoing emergency surgery, those with peri‐operative SARS‐CoV‐2 infection have only a slight increase in VTE risk compared with those without (OR = 1.26).…”
Section: Effect Of Venous Thromboembolismsupporting
confidence: 89%
“…Cardiovascular complications are distributed in various forms of COVID-19 and various populations [ 125 , 126 , 127 , 128 ]. The tendency is to be cautious with repurposed drugs administration, for COVID-19.…”
Section: Two Pivotal Questions To Find a Balance Between Cardiovascul...mentioning
confidence: 99%
“…First, the samples of the study were obtained from one tertiary hospital in Shanghai and so was limited as a single-center study. Second, data collection was performed before the COVID-19 pandemic; however, the latest study from the COVIDSurg Collaborative group demonstrated that SARS-CoV-2 infection was also a significant predictor of DVT in critically ill patients (24). Therefore, it will be more meaningful to explore the optimal prophylaxis and treatment protocols for DVT in combination with the above risk factors in the setting of the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%